Analysis of Occupational Safety and Health in the Production Process Section Using the Failure Mode And Effect Analysis (FMEA) Method at PT Mitra Mandiri Perkasa - HM, Gatot Basuki (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2021)
Based on the results of the analysis carried out, it was found that there were 29 work accidents in the turning wood production process for a period of 3 years, then after the classification was carried out based on the company's working environment conditions obtained 5 categories of work accidents. The results of the calculation of the risk prority number (RPN) show that the potential failure with the highest RPN level is that the hand is exposed to wood on the rip saw machine with an RPN value of 140. Proposed improvement is that machine operators must use PPE when doing work, provide a grace period when moving raw materials to rip saw machines to provide space for workers, routine inspections and always moving materials after being processed in the rip saw machines and giving danger signs in the production process area, improving standard operational procedures and periodic supervision in accordance with the applied K3 procedures.